The amino terminus of PKA catalytic subunit: a site for introduction of posttranslation heterogeneities by deamidation : D‐Asp2 and D‐isoAsp2 containing isozymes - Kinzel, Volker; Bossemeyer, Dirk; Pipkorn, Rüdiger; Lehmann, Wolf-Dieter (Protein science, 2008)
Conserved deamidation of PKA catalytic subunit isozymes Cα and Cβ—more than 25% at Asn2 in vivo in both cases—has been shown to yield Asp2‐ and isoAsp2‐containing isozymes (Jedrzejewski PT, Girod A, Tholey A, König N, Thullner S, Kinzel V, Bossemeyer D, 1998, Protein Sci 7: 457–469).
First published online: 31 December 2008
Elektronische Reproduktin der Druck-Ausgabe
Gesehen am 23.02.2021